Mass Communication Strategy in Encouraging the Adoption of a Healthy Lifestyle in Society - Ariana, Patricia Margy; Clarashiva, Adina; Pakaya, Silvana Stela (Ilomata International Journal of Social Science, 2024)
Healthy lifestyle has become the main focus in efforts to prevent the increasing prevalence of non-communicable diseases in society. In this context, mass communication strategies play a central role in forming awareness and encouraging the adoption of a healthy lifestyle. This research aims to explore and analyze mass communication strategies that are effective in changing people's behavior regarding healthy lifestyles. The main objective of this research is to identify the most effective mass communication strategies in encouraging the adoption of healthy lifestyles in society. In addition, this study aims to evaluate the impact of this strategy on the level of awareness and behavior change regarding various aspects of a healthy lifestyle. This research uses the literature review method as an analytical framework. Data was collected from various sources such as scientific journals, articles and books related to mass communication strategies and healthy lifestyles. Data analysis involves detailing the various mass communication strategies that have been implemented and identifying patterns of success in changing people's behavior. the use of N.Vivo analysis can help in identifying patterns, trends, and relationships between various concepts and findings that emerge from these articles. \The research results show that mass communication strategies that rely on interesting narratives, effective use of social media, and involvement of community leaders have a significant impact in encouraging the adoption of a healthy lifestyle. The ability to create community engagement and respond to local cultural dynamics also plays an important role in the success of this strategy.